Desenvolvimento de modelos preditivos de qualidade e determinação de padrões mínimos de qualidade de melões e melancias comercializadas no Brasil - Carvalho, Ezequiel Malfitano (2016)
The variation of the quality of fruits currently sold in Brazil affects the marketing and leads to consumer dissatisfaction as a result of the failure to establish a minimum quality standard. The establishment of minimum quality standards can be achieved through rapid and easy physical and physicalchemical analysis, which show good correlation with sensory attributes. The objective of this work was to monitor the quality of 'Yellow' melon and watermelon (cv Crimson Sweet) marketed by CEASA Minas, located in Contagem, Minas Gerais, Brazil, in different seasons. We also aimed at establishing a minimum quality standard for 'Yellow' melons and watermelon (cv Crimson Sweet), developing predictive models based on sensory consumer acceptance. The variables associated with quality were: pH, soluble solids (SS), titratable acidity (TA), firmness, diameter, respiration, peel color, pulp, juice and juice yield. The sensory acceptance notes of the consumers were calibrated with physicochemical variables through multiple linear regressions in order to build a predictive model. Therefore, a note to the minimum standard of quality fruit based on the results of sensory analysis was established. There was wide variation in the quality variables of the fruit throughout the study. Univariate prediction models were not significant since the multivariate models showed good functionality. Therefore, multivariate models were obtained, considering all the studied variables (pH, TA, SS, SS/TA, firmness, L*, a*, b*, Chroma, °h % and juice). Finally, a General Standard Minimum Quality for 'Yellow' melon and watermelon (cv Crimson Sweet) was obtained based on the overall impression notes of the consumers. The minimum standard of association with the obtained models can be used to predict sensory consumer acceptance through easy and simple physical and physicochemical measurements, making sure that the product being sold is or is not within the established Minimum Standard Quality standards.